Sintering behavior of periclase–doloma refractory mixes - Tomba Martinez, Analia Gladys (2009)
Steelmaking electric arc furnaces (EAF) hearth is usually built up with dry vibratable refractory mixes. During furnace operation, the refractory mix undergoes sinterization, slag attack, and chemical interaction with steel. Material sintering is needed in the upper part of the EAF hearth, in order to develop enough mechanical strength and wear resistance during operation. Densification of the upper layer also reduces steel infiltration from the hot surface. In this work, the sintering behavior of three dry vibratable commercial refractory materials for EAF hearth is reported. The characterization of the mixes includes chemical, mineralogical, and granulometric analyses. The study of sintering behavior is carried out by dilatometric analysis and microstructural and mechanical evaluation of sintered specimens. Results showed that the analyzed mixes mainly contain periclase and doloma, with a wide granulometric distribution and different content of minor components (mainly, iron oxides). Material sintering began at temperatures higher than 1200 °C and was associated to liquid phase formation. Differences in sintering mechanisms with distinct amounts of liquid phase involved were determined in the analyzed materials and related to their iron oxides contents. Well-sintered specimens with higher room temperature mechanical strength and lower porosities were obtained from the mix with highest iron oxide content.